Graphene Oxide Hybrid Supramolecular Hydrogels with Self‐Healable, Bioadhesive and Stimuli‐Responsive Properties and Drug Delivery Application. Issue 8 (7th June 2018) - Chen, Yunhua; Cheng, Wenhua; Teng, Lijing; Jin, Min; Lu, Bingheng; Ren, Li; Wang, Yingjun
Abstract: Self‐healable hydrogels are promising soft materials with great potential in biomedical applications due to their autonomous self‐repairing capability. Although many attempts are made to develop new hydrogels with good self‐healing performance, to integrate this characteristic along with other responsive multifunctions into one hydrogel still remains difficult. Here, a self‐healable hybrid supramolecular hydrogel (HSH) with tunable bioadhesive and stimuli‐responsive properties is reported. The strategy is imparting graphene oxide (GO) nanosheets and quadruple hydrogen bonding ureido‐pyrimidinone (UPy) moieties into a thermoresponsive poly( N ‐isopropylacrylamide) (PNIPAM) polymer matrix. The obtained GO–HSH hydrogel shows rapid self‐healing behavior and good adhesion to various surfaces from synthetic materials to biological tissue. In addition, doxorubicin hydrochloride (DOX) release profiles reveal the dual thermo‐ and pH‐responsiveness of the GO–HSH hydrogel. The DOX‐loaded hydrogel can further directly adhere to titanium substrate, and the released DOX from this thin hydrogel coating remains biologically active and has high capability to kill tumor cells. Abstract : A graphene oxide hybrid supramolecular hydrogel is reported that possesses rapid self‐healing ability, tunable adhesiveness, and dual stimuli responsiveness. The hydrogel can self‐heal with mechanical recovery completed within seconds and has remarkable adhesion to various surfaces and biological tissues. The hydrogel can be used as an adhesive coating for localized drug release and anticancer treatment.